ANALYSIS OF MATHEMATICAL COMMUNICATION SKILLS OF JUNIOR HIGH SCHOOL STUDENTS OF COASTAL KOLAKA - Ahmad Rustam; Andi Mariani Ramlan (USN Kolaka, 2017)
Mathematical Communication Skills (MCS) of Junior High School students in General is stillvery lacking. Does it happen to students coming from the coast? The purpose of this research is to identify and analyze the Mathematical Communication Skills of junior high school students of Kolaka Regency. The data in this research is the data of test result of students' Mathematical Communication Skills and interview result. The instrument used is a description test. The results of analysis of Mathematical Communication Skills of coastal students in Kolaka regency as a whole is still categorized low and for each of the three indicators are also categorized as low. Three KKM indicators of students, if ranked from the lowest acquisition respectively is the ability indicators Com3, the ability Com1, then Com2